Transformation of Labor Law in the Modern Era: Balancing the Protection of Workers' Rights and Certainty of Obligations in Industrial Relations - M Nabil Alifah; Andre Kurniawan; Alfa Cygni; Muhammad sobri (Jurnal Cendikia ISNU SU, 2024)
Digital transformation has changed the character of industrial relations through the development of flexible work systems, the digitization of work processes, and the emergence of new labor relations models that demand adjustments to labor laws. These changes pose a challenge in maintaining a balance between the protection of workers' rights and the certainty of the obligations of the parties amid the need to increase productivity and competitiveness in the business world. This research aims to analyze the transformation of labor law in the modern era and examine the extent to which legal arrangements in Indonesia are able to realize a balance between workers' rights and obligations in industrial relations. The research uses a normative juridical method with a legislative approach and a conceptual approach. Primary, secondary, and tertiary legal materials were obtained through literature studies, then analyzed qualitatively using prescriptive analysis methods. The results of the study show that technological developments have shifted the paradigm of employment relations from the conventional system to a more flexible and digital-based employment relationship, thus affecting the implementation of the rights and obligations of workers and employers. Although Law Number 6 of 2023 has accommodated some of these changes, regulations regarding flexible work systems, digital platform-based workers (gig economy), and protection for workers outside working hours still need to be strengthened in order to be able to provide legal certainty. Thus, the effectiveness of labor law in the modern era depends on its ability to build a balance between the protection of workers' rights, the certainty of the obligations of the parties, and the needs of the business world in dealing with the dynamics of digital transformation.